Analysis of Tourism Carrying Capacity as a Basis for Development of the Tanjung Tampa Nature Tourism Park, Central Lombok Regency - Nursyam, Alvin Sofiandi; Budastra, Ketut; Sukardi, Lalu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The development of the Tanjung Tampa TWA into a natural tourism destination that can support one of the priority national tourism destinations in the Mandalika Special Economic Zone (KEK) must pay attention to the carrying capacity of the Tanjung Tampa TWA so that it does not cause negative impacts that can damage the biophysics of the area. This research aims to analyze the tourism carrying capacity of Tanjung Tampa TWA using the Cifuentes method. The research results show that the physical carrying capacity is 4720 tourists per day, the real carrying capacity is 161 tourists per day and the effective carrying capacity is 121 tourists per day. The development of the Tanjung Tampa TWA by taking into account the results of the tourism carrying capacity analysis can be done by increasing the quantity of human resources. Improvements can be made by empowering communities around the Tanjung Tampa TWA area, improving the quality of community human resources by establishing and assisting natural tourism interpreters.